If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 869 = (6(x + 8)) Reorder the terms: 869 = (6(8 + x)) 869 = ((8 * 6 + x * 6)) 869 = ((48 + 6x)) 869 = (48 + 6x) Remove parenthesis around (48 + 6x) 869 = 48 + 6x Solving 869 = 48 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 869 + -6x = 48 + 6x + -6x Combine like terms: 6x + -6x = 0 869 + -6x = 48 + 0 869 + -6x = 48 Add '-869' to each side of the equation. 869 + -869 + -6x = 48 + -869 Combine like terms: 869 + -869 = 0 0 + -6x = 48 + -869 -6x = 48 + -869 Combine like terms: 48 + -869 = -821 -6x = -821 Divide each side by '-6'. x = 136.8333333 Simplifying x = 136.8333333
| d-2c=-3 | | 8x^2+4x+12=0 | | 2/7x21/4 | | 12=-3-5x | | X^2+y^2-10x-4y-20=0 | | 1|3c=3/8 | | 89x72/ | | -25x+5y=25 | | -0.6=1.4+1.4+x | | 2sin^2x-3cos=3 | | (x^20-y^14)= | | -30=2y | | 14x=8(x+3) | | 4(-1x-3)=20 | | -x^2-2x+6=2x^2+5x+3 | | B/8=-6 | | 2[9.5(6)]+2[14.2(9.5)]+2[14.2(6)]= | | 28-6x=11-9x | | -6(3x+6)=-198 | | -6(x-2)=8(x+5) | | 4=2m-m | | 4(-5x-1)=76 | | 6(-3x+6)=36 | | (18x^2)-12x-12=0 | | p-3+p=-5 | | x^2+14x+52=3 | | 7(6x-5)=469 | | 4x-3x+12=24 | | -3(-3-2x)=81 | | 6x-20y+14=0 | | 4x-3x-12=24 | | X=12x-7 |